APLIKASI PEMBELAJARAN TERHADAP ANAK BERPERILAKU MENYIMPANG - Syarifan Nurjan (MUADDIB Jurnal Kependidikan dan Keislaman, 2014)
Learning program for children who have deviant behavior becomes a pressure for education. The identification of those deviant behavior cases can be made as a standard in using the learning program that leads to intervensions, especially to reduce or even eliminate the deviant behavior, both with psychoanalytic which gives more emphasis on psychodinamic, psychoeducational, humanistics and echological and the behavior which its healing approach is by modifying the behavior to the most correct one. The learning aplication is by using the lesson plan and some steps of creating a lesson plan consisting of doing the screening or test to determine the level of psychomotor functional development with the Geddes Psychomotor Inventory (GPI) instrument profile I and II as a pretest, analyzing all the screening results or pretest with the GPI instrument profile I and II, and making a motion pattern, arranging a lesson plan which is appropriate to the children need, and conducting the final learning evaluation.